Aspectos biológicos e tabela de vida de fertilidade de Aphis gossypii Glover (Hemiptera: Aphididae) em cultivares de algodoeiro DeltaOPAL e NuOPAL - Funichello, M. [UNESP] (2012)
Genetically modified plants can affect the biology of non-targeted organisms, and change the tritrofic relations in the agro-ecosystem. Bt cotton cultivars have led to changes in the biology of Aphis gossypii Glover (Hemiptera: Aphididae), and have influenced the population dynamics of this insect in the field. The objective of the present study was to assess some biological parameters of A. gossypii in genetically modified cotton NuOPAL (Bollgard I) and DeltaOPAL cultivars. The experiment was carried out under controlled conditions, at 25 ± 1º C, 70 ± 10% relative humidity, and a 12-hour photophase. The experiment was installed in a completely randomized design, with DeltaOPAL and NuOPAL (Bollgard I) cultivars considered treatments, and 40 replications. Leaf circles of 6 cm in diameter were placed into Petri dishes containing 1% solidified agar-water, and nymphs of up to one-day-old were placed individually on these circles. The evaluations were carried out on a daily basis, and the biological parameters evaluated were: duration of each nymph stage and total phase, duration of reproductive and post-reproductive periods, total nymphs/females, and longevity. The parameters of the fertility life table were also assessed. The duration of nymph states and nymph stages, duration of reproductive and post-reproductive periods, longevity, fertility and total number of nymphs per female did not present any significant differences. The genetically modified NuOPAL does not affect the biology of the cotton aphid A. gossypii.